The Role of Cloud Computing and Big Data in Enhancing E-Learning Service Quality - Sari, Annisa Wulan (Universitas Komputer Indonesia, 2025)
The transition to digital education has exponentially increased the demand for robust, scalable, and personalized e-learning platforms. Legacy educational systems often struggle with server overloads, limited storage capacity, and the inability to process massive amounts of student data. This study explores the integration of Cloud Computing and Big Data analytics as a strategic solution to enhance e-learning service quality. Through a qualitative approach and thematic analysis of recent literature, this paper identifies that Cloud Computing provides a highly scalable, cost-effective infrastructure that ensures continuous system availability. Concurrently, Big Data empowers educational institutions to analyze student learning behaviors, predict academic outcomes, and deliver personalized learning experiences. The findings suggest that the synergy between these two technologies not only resolves technical bottlenecks but also transforms passive e-learning environments into adaptive, student-centric ecosystems. This study provides a comprehensive framework for higher education institutions aiming to modernize their IT governance and instructional delivery.